Quantitative Strategic Planning Matrix Dalam Penentuan Strategi Tata Kelola Air Sebagai Implementasi Green Campus Di Kampus UKSW - Cahyaningrum, Desti Christian (Jurnal Green Growth dan Manajemen Lingkungan, 2024)
Conservation, recycling, and saving of water are kinds of green campus implementation that necessary in daily basis on campus life. This is because of water consumption in the campus environment is quite large and has the potential to cause degradation of water resources. This research aims to analyze internal and external factors that can support or hinder the implementation of a green campus at UKSW based at the water management criteria in the UI GreenMetric. Resullts of external and internal factor identification then used for arranged water management strategies using the Quantitative Strategic Planning Matric (QSPM) approach. The result show that the current position of UKSW water management is still in the "grow" and "build" phase at Internal-External (I-E) matrix, with IFE score of 2.549 and the EFE score of 3.368. Therefore, the most suitable strategy to implement is an intensive and integrative strategy referring to IFE and EFE. There are 15 strategies that have been successfully developed. That are consist of 5 S-O strategies; 5 W-O strategies, 3 S-T strategies, and 2 W-T strategies. The strategy with the highest Total Atractiveness Score (TAS) is allocating funds to empower UKSW human resources in the context of developing water and rainwater recycling technology as a form of implementing a green campus while also supporting participation in the UI GreenMetric ranking (TAS = 2.797)